Perancangan Bilah Tipe Inverse Taper Pada Turbin Angin Berdasarkan Kondisi Angin Di Pekanbaru - Hatta, Muhammad; Martin, Awaludin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The increasing consumption of fossil fuels as energy source of the world cause a decrease in a number of fossil fuels. Wind energy as one of renewable energy resource has a great potential to solve the problem of dependency on fossil fuels, especially in Pekanbaru, Indonesia. Pekanbaru wind speed condition which is considered relatively low can be harnessed efficiently by designing blades which suits wind characteristics in Pekanbaru.  Blades are designed using aerodynamic equations and  software assistance such as Microsoft Excel, Qblade, and Autodesk Inventor. As a result, the blades had a solid structure, easily in manufacturing and affordable which can generate mechanical power at low wind speeds with a radius 1,1 m and hub 0,2 m and the chord length  at the base of  the blade 0,13 m and at the tip 0,26 with twist angle at the base of the blade 20,4  and at the tip 5,6  . The result of this research is to show that the inverse taper blade design is applicable in low wind speed conditions in order to produce an affordable, compact, and efficient wind turbine appropriate for wind characteristic in Pekanbaru. Keyword : Chord, Twist Angle, Blades, Inverse Taper, Wind Turbine